2020
DOI: 10.1155/2020/5146253
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Side of Onset and Cerebral Regional Homogeneity in Parkinson’s Disease: A Resting-State fMRI Study

Abstract: Objective. Motor symptoms are usually asymmetric in Parkinson’s disease (PD), and asymmetry in PD may involve widespread brain areas. We sought to evaluate the effect of asymmetry on the whole brain spontaneous activity using the measure regional homogeneity (ReHo) through resting-state functional MRI. Methods. We recruited 30 PD patients with left onset (LPD), 27 with right side (RPD), and 32 controls with satisfactory data. Their demographic, clinical, and neuropsychological information were obtained. Restin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Dopamine insufficiency in the nigrostriatal pathway may cause decreased ReHo values in the motor cortex [31]. Decreased ReHo in this region of Parkinson's patients has been reported in several studies [32,33]. A meta-analysis of ReHo in PD reported that ReHo is decreased in the right precentral gyrus (premotor cortex extending to the primary motor cortex, M1) in patients compared with normal controls [34].…”
Section: Pd (N=20) Nc (N=20) T/χ 2 Pmentioning
confidence: 97%
“…Dopamine insufficiency in the nigrostriatal pathway may cause decreased ReHo values in the motor cortex [31]. Decreased ReHo in this region of Parkinson's patients has been reported in several studies [32,33]. A meta-analysis of ReHo in PD reported that ReHo is decreased in the right precentral gyrus (premotor cortex extending to the primary motor cortex, M1) in patients compared with normal controls [34].…”
Section: Pd (N=20) Nc (N=20) T/χ 2 Pmentioning
confidence: 97%
“…Further, high miR-16-1 levels block the translation of the HSP70 (heat shock protein 70) mRNA, involved in α-synuclein inhibition, thus leading to an accumulation of α-synuclein [ 84 ]. Moreover, targeting miR-7, miR-153, and miR-34b/c from binding on their α-synuclein induces elevated levels of α-synuclein [ 85 , 86 ].…”
Section: Msc-secretome: Mirna Relevance and Theranostic Applicatiomentioning
confidence: 99%
“…Below we list the disorders followed by the brain area in which a difference was found. In recent researches, increased or decreased REHO in certain brain regions has been associated with Methamphetamine Dependence (Yu et al, 2020), Parkinson’s Disease (Liu et al, 2019b; Li et al, 2020), Drug-Naive Bipolar Disorder (Shan et al, 2020), Schizophrenia (Ji et al, 2020), psychiatric disorders (Wei et al, 2020), seizures (Liu et al, 2019a), obsessive-compulsive disorder (Yang et al, 2019), manic pediatric bipolar disorder (Xiao et al, 2019), white matter hyperintensities and cognitive impairment (Ye et al, 2019), Strabismus and Amblyopia (Shao et al, 2019) and corneal ulcer (Xu et al, 2019), psychiatric disorders (Wei et al, 2020), Alzheimer (Cheng et al, 2019), Vascular mild cognitive impairment (Zuo et al, 2019). Figure 1 demonstrate brain regions where REHO is most associated to mental disorders or other diseases mentioned in recent REHO researches.…”
Section: Introductionmentioning
confidence: 99%